Interaction of atypical cadherin Fat1 with SoHo adaptor proteins CAP/ponsin and ArgBP2 - Braun, Gerald S.; Kriz, Wilhelm (Biochemical and biophysical research communications, 2016)
Mammalian Fat1 is a giant atypical cadherin/tumor suppressor involved in the regulation of cellular orientation, migration, and growth. Fat1 is implicated in the development of the brain, eye, and kidney. Altered expression or mutations of FAT1 are also associated with cancer and facioscapulohumeral muscular dystrophy (FSHD). Yet, the mechanistic functions of this pathway remain incompletely understood. Here, we report the identification of Sorbin-homology (SoHo) proteins as novel interaction partners of Fat1 by virtue of a yeast-two-hybrid screen. SoHo proteins play diverse roles as adaptor proteins in cell signaling, cell adhesion and sarcomere architecture, including altered expression in cancer and FSHD. Specifically, we found SoHo proteins CAP/ponsin-1 and -2 (Sorbs1) and ArgBP2 (Sorbs2) to interact with the cytoplasmic domain of Fat1. We mapped the interaction to a prolin-rich classic type II PXXP motif within Fat1 and to the three Src-homology (SH3) domains within SoHo proteins using mutant expression in yeast, pulldown assays, and cell culture. Functionally, endogenous ponsin-2 expression of NRK-52E cells at cellular leading edges was lost upon knockdown of Fat1. In summary, our data point to an interaction of Fat1 with SoHo proteins that is able to recruit SoHo proteins to sites of Fat1 expression.